GAMBARAN KONSUMSI SUMBER VITAMIN DAN MINERAL, STATUS GIZI, DAN KEJADIAN DISMENOREA PADA REMAJA PUTRI DI SMP SHAFIYYATUL AMALIYYAH TAHUN 2015 - Fitratur Rahmah Agustina; Ernawati Nasution; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Dysmenorrhea is the complaining of pain comes from lower abdomen and when menstruation, the pain feel about 2 or 3 years after menarche. Dysmenorrhea incidence have ranges from 45% to 75% of all adolescents puberty and it lead to absenteeism from school or work environment. Nutritional status and intake of vitamins and minerals in adolescents need to be considered because it can affect the occurrence of complaints during menstruation, called dysmenorrhea. The purpose of this study was to see from the prespective of the consumption of vitamins and minerals, and nutritional status and the incidence of dysmenorrhea to adolescents in junior high school Shafiyyatul amaliyyah 2015. The type of research in this study is using desctriptive. The population of study was around the junior high school students Shafiyyatul amaliyyah with total 133 students. Samples taken as many as 44 students with simple random technique. Data collected by interview using a food recall form 24 form food frequency, weighing and height measurement. The survey results revealed that the incidence of dysmenorrhea most complaining by adolescents are at a moderate level as many as 21 people (47,7%). The intake of vitamin B6 is lacking in adolescents by 47,1% with moderate pain complaints. Intake of vitamin E were less in all adolescents in which 47,7% of the experienced moderate pain. The intake of calcium is less amounted to 50,0% of respondents with moderate pain complaints. The intake of zinc is less by 47,5% of respondents complaining of mild pain. Normal nutrition status of adolescents by 50,0% had mild pain complaints. Adolescents of Shafiyyatul amaliyyah junior high school sugested to consuming food sources that high of vitamins and minerals regularly, especially foods containing vitamin B6, vitamin E, calcium and zinc. Keywords: Consumption of vitamins and minerals, nutritional status, dysmenorrhea, adolescents